POLA PERILAKU PENGAMEN JALANAN TERHADAP MASYARAKAT PENGGUNA JALAN RAYA KOTA PADANG - Joef, Anrian; Pramono, Wahyu; Elvawati, Elvawati (Pendidikan Sosiologi, 2013)
This study discusses patterns of behavior of street singers to highway users is an issue that makes people uneasy in the existence of buskers on the street, because the street singers often perform deviant acts, such as making follow- kejahataan and forcing people . This study aimed to describe the behavior patterns of street singers to the public highway users Padang. Researchers used social exchange theory ( Reward and Phunisment ) proposed by George C. Homans, which is a simple economic principles such as the costs, rewards and prizes.This study uses qualitative research methods with descriptive type. The study site is on Jl Imam Bonjol and Jl. Veteran city of Padang. This study is an attempt to create a description, a picture of a situation as it should. Decision informants in this study use the two techniques, namely the purposive sampling and incidental sampling. The type of data in this study is primary data and secondary data were collected through observation, interviews, and documentation. Data analysis technique used is an interactive model of analysis proposed by Miles and Huberman (1984 ).From this study it can be concluded that the pattern of behavior in accordance with other street musicians living conditions are far from normative life, which shape the behavior of singers that are not in accordance with the social norms and values prevailing in society, so that people feel disturbed by buskers with their behavior in the streets: First, too pushy in asking for reward. Second, talk rude and disrespectful. Third , random singers in singing. Fourth, do not look good.